Cataract in leprosy patients: cataract surgical coverage, barriers to acceptance of surgery, and outcome of surgery in a population based survey in Korea. Issue 6 (1st June 2001) - Courtright, Paul; Lewallen, Susan; Tungpakorn, Narong; Cho, Byeong-Hee; Lim, Young-Kyu; Lee, Hyun-Ji; Kim, Sung-Hwa
Abstract : BACKGROUND/AIMS: Cataract is the leading cause of blindness in leprosy patients. There is no population based information on the cataract surgical coverage, barriers to use of surgical services, and outcome of surgery in these patients. We sought to determine these measures of cataract programme effectiveness in a cured leprosy population in South Korea. METHODS: The population consisted of residents of six leprosy resettlement villages in central South Korea. All residents were invited to participate in a study of eye disease and interviewed regarding use of surgical services and reasons for not using these services. RESULTS: The cataract surgical coverage in this population was 55.4% when <6/18 was used as the cut off and increased to 78.3% when the cut off was <6/60. Barriers reported by patients included being told by the doctor that the cataract was not mature and a perception by the patient that there was no need for surgery. Among patients who had aphakic surgery, 71% were still blind in the operative eye while among patients who had pseudophakic surgery, 14% were still blind (presenting vision). Blindness in pseudophakic patients could be reduced to 3% with spectacle correction. CONCLUSION: Cataract prevalence in leprosy patients will increase as life expectancy continues to increase. Leprosy control programmes will need to develop activities aimed at reducing the burden of cataract. Recommendations include establishing collaborative agreements with ophthalmological services to provide high quality IOL surgery to these patients, training of health staff to identify and refer patients in need of surgery, monitoring the uptake of cataract surgery among patients needing services, and monitoring the outcome of surgery to improve refractive outcome.